Does Current Practice in the United States of Carotid Artery Stent Placement Benefit Asymptomatic Octogenarians? - Young, K.C. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: CAS or CEA for asymptomatic carotid stenosis is the focus of recently completed and ongoing randomized clinical trials. These techniques are widely utilized outside the setting of such trials. Therefore, our goal was to analyze the in-hospital stroke or death rates after CAS or CEA for asymptomatic stenosis that reflect current nationwide practice. MATERIALS AND METHODS: Using sample-weighted ANOVA, we analyzed records from the 2006 and 2007 NIS, which are nationally representative cohorts for asymptomatic CAS or CEA. The primary outcome measure was a composite end point of in-hospital stroke, cardiac complications, or death. In-hospital stroke or death was a secondary outcome measure. RESULTS: For ≥80 years of age, the in-hospital stroke, cardiac complications, or death rate after CAS was 4.9%, while the complication rate after CEA was 3.8%. The stroke or death rate after CAS was 2.7% for ≥80 years of age and was 1.5% after CEA for the same age group. Multivariate analysis showed that age (OR, 1.12; 95% CI, 0.97–1.3; P < .07) or procedure (OR, 1.12; 95% CI, 0.99–1.27; P < .14) was not associated with the composite end point of in-hospital stroke, cardiac complications, or death. In contrast, CAS (OR, 1.28; 95% CI, 1.03–1.58) and female sex (OR, 1.23; 95% CI, 1.04–1.45) were independently associated with in-hospital stroke or death following asymptomatic carotid revascularization. Hospital charges and hospital costs were lower for CEA than CAS (2007 costs: $7779 versus $12,104). CONCLUSIONS: CAS is independently associated with increased in-hospital stroke or death (excluding cardiac complications from the composite outcome). In those ≥80 years of age, CAS as currently performed may not improve the natural history of asymptomatic carotid stenosis, because in-hospital stroke or death rates following CAS approached 3% in this group.